Telomere length as a biomarker of exposure to indoor woodstove smoke in rural Honduras: a feasibility field study - Altina, Noelia, author; DeLuca, Jennifer, advisor; Bailey, Susan, advisor; Ross, Eric, committee member; Clark, Maggie, committee member (Colorado State University. Libraries, 2017)
Telomeres, the natural ends of linear chromosomes, are important for maintaining genome stability. Telomere length is an inherited trait influenced by a host of lifestyle and environmental factors, which have been shown to accelerate the rate of telomere shortening, and thus of aging. Indoor air pollution is one of the environmental factors known to influence the length of telomeres. It has been reported that people exposed to this kind of contamination, have an increased risk for pulmonary diseases, cardiovascular diseases and cancer. The accumulation of evidence correlating telomere length with different diseases and chronological age supports the use of short telomere frequency as an informative biomarker of general health status and aging. Epidemiological studies suggest that increased frequencies of nuclear aberrations (micronuclei, buds) are also correlated with exposure to air pollution.

Here, we confirm the feasibility of conducting field studies to evaluate telomere length in populations exposed to indoor air pollution in rural Honduras, and begin to address the question of whether telomere length can be used as an informative biomarker of exposure to indoor woodstove smoke. Buccal mucosa basal (stem-like) cells were collected from 100 exposed individuals in the field (prior to intervention); samples were shipped to US (CSU) for assessment of average telomere length (TL) and frequency of short telomeres. Results were correlated with age for all participants, and with total number of nuclear aberrations in a subset (20 individuals). Initial analyses suggest that frequencies of short telomeres, rather than average telomere length, correlate with total number of nuclear aberrations in those assumed to be the most exposed individuals. These preliminary findings require correlation with actual particulate matter exposures, as well as confirmation in a larger cohort (studies on-going).
Keywords: interphase Telo-FISH; stem-like cells; biomarker; total nuclear aberrations; short telomere percentage